2022
DOI: 10.11113/aej.v12.17520
|View full text |Cite
|
Sign up to set email alerts
|

Single Piles and Pile Groups Capacity in Unsaturated Sandy Clay Based on Laboratory Test

Abstract: Pile capacity is one of the controlling factors in the foundation design. In this study, compression and tension tests were carried out on model piles driven in sandy clay in a test box. The diameter of concrete single-pile models was 16 mm, with ratios of 6, 10, 15 and 20 for pile length (L) to diameter (d). The diameter and length of concrete pile group models were 10 mm and 200 mm, respectively, with four different configuration groups, i.e., single pile, two piles (2×1), three piles (triangle), and four pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Heni, [13] performed compression tests on piles that were driven in sandy clay prepared with three different water contents. The results showed that the resistance of single piles under compressive loads affect by the increase of matric suction and slenderness ratio (L/D).…”
Section: Introductionmentioning
confidence: 99%
“…Heni, [13] performed compression tests on piles that were driven in sandy clay prepared with three different water contents. The results showed that the resistance of single piles under compressive loads affect by the increase of matric suction and slenderness ratio (L/D).…”
Section: Introductionmentioning
confidence: 99%